2023
DOI: 10.1002/ajmg.a.63119
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of first noncoding exon in ANKRD11 leads to KBG syndrome

Abstract: Phenotypic features of KBG syndrome include craniofacial anomalies, short stature, cognitive disability and behavioral findings. The syndrome is caused by heterozygous pathogenic single nucleotide variants and indels in ANKRD11, or a heterozygous deletion of 16q24.3 that includes ANKRD11. We performed genome sequencing on a patient with clinical manifestations of KBG syndrome including distinct craniofacial features as well as a history of mild intellectual disability and attention‐deficit hyperactivity disord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Previous studies have demonstrated that pathogenic ANKRD11 missense variants or three-base pair deletions resulting in a single-amino-acid deletion did not significantly impact the expression levels of mRNA and protein, as well as nuclear localization, but impair the stability or transcriptional activity of encoded protein, particularly missense variants clustered in the C-terminal repression domain 2 (RD2) [ 28 , 30 ]. In contrast, deletion of first noncoding exon obviously decreased the mRNA level of ANKRD11 [ 32 ]. Taken together, ANKRD11 frameshift variant (c.2280_2281delGT) appeared to trigger more substantial damage to the gene/protein compared to other variant types.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that pathogenic ANKRD11 missense variants or three-base pair deletions resulting in a single-amino-acid deletion did not significantly impact the expression levels of mRNA and protein, as well as nuclear localization, but impair the stability or transcriptional activity of encoded protein, particularly missense variants clustered in the C-terminal repression domain 2 (RD2) [ 28 , 30 ]. In contrast, deletion of first noncoding exon obviously decreased the mRNA level of ANKRD11 [ 32 ]. Taken together, ANKRD11 frameshift variant (c.2280_2281delGT) appeared to trigger more substantial damage to the gene/protein compared to other variant types.…”
Section: Discussionmentioning
confidence: 99%